2021
DOI: 10.1001/jamanetworkopen.2021.3520
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity With Survival Outcomes in Patients With Cancer

Abstract: IMPORTANCE Obesity, defined as a body mass index (BMI) greater than 30, is associated with a significant increase in the risk of many cancers and in overall mortality. However, various studies have suggested that patients with cancer and no obesity (ie, BMI 20-25) have worse outcomes than patients with obesity.OBJECTIVE To assess the association between obesity and outcomes after a diagnosis of cancer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
193
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(206 citation statements)
references
References 273 publications
10
193
1
2
Order By: Relevance
“…Also, molecular mechanisms connecting obesity with PC and other urothelial cancers have been broadly established [84]. Finally, the relationship with PC outcomes met analogy criterion, as obesity has been linked for the last three decades to mortality from numerous types of cancer [11,85] and to other outcomes related to PC, for instance, the presence of metastases [86]. Therefore, objectively, several criteria for causation were met.…”
Section: Discussionmentioning
confidence: 99%
“…Also, molecular mechanisms connecting obesity with PC and other urothelial cancers have been broadly established [84]. Finally, the relationship with PC outcomes met analogy criterion, as obesity has been linked for the last three decades to mortality from numerous types of cancer [11,85] and to other outcomes related to PC, for instance, the presence of metastases [86]. Therefore, objectively, several criteria for causation were met.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] However, there are studies that postulate a biologic rational for the improved survival seen in obese patients with renal cell carcinoma. 13,27,28 In those studies, the authors found that patients with renal cell carcinoma and obesity had longer overall survival than patients without obesity. One hypothesis based on transcriptomic signature differences in the primary tumor and the peritumoral adipose tissue is that increased tumor angiogenesis and increased peritumoral inflammation in the perirenal white adipose tissue of obese patients contribute to their survival advantage.…”
Section: Obesity Adiposity and Cancer Risk And Prognosismentioning
confidence: 99%
“…12 Accumulating data also suggest that obesity is associated with higher rates of cancer progression, recurrence, and mortality, especially for breast, prostate, and colon cancer. 13,[16][17][18][19][20] Furthermore, cancer survivors are at higher risk of becoming obese, 21 likely because of various factors, including the use of chemotherapy, steroids, and hormonal therapy, which can accelerate weight gain. 22 Although the obesity paradox refers to studies demonstrating that obesity is associated with improved overall survival, this is more likely secondary to flaws in methodological mechanisms, such as using body mass index as an obesity measure, confounding and reverse causality.…”
Section: Obesity Adiposity and Cancer Risk And Prognosismentioning
confidence: 99%
“…Of note, while a large body of evidence strongly supports the notion that obesity increases the risk of incident ccRCC in the general population, elevated BMI has also been associated with better prognosis among those patients who are already diagnosed with ccRCC [ 97 , 98 , 99 ]. This “obesity paradox” is not unique to kidney cancer, having been described in other neoplasms, such as lung cancer and melanoma [ 100 , 101 , 102 ], as well as in non-neoplastic diseases, such as chronic heart failure and coronary artery disease [ 103 ]. Obesity appears to be associated with better outcomes in those patients with RCC who undergo surgical or pharmacologic treatment, with less evidence available for such an effect in patients with untreated RCC [ 104 , 105 ].…”
Section: Exploring the Link Between Obesity And Renal Cell Carcinomamentioning
confidence: 99%